Empowering Math Learning with Android: Ethnomathematics Media for 3D Shapes in Elementary Education - Nur Julianto; Agus Efendi; Gunarhadi (Universitas Pendidikan Ganesha, 2024)
The use of smartphones in learning activities holds great potential, especially through Android-based learning media, which allows smartphones to serve as tools for operating learning media in the educational process. This potential is further supported by the characteristics of today's students, who are accustomed to gadgets in their daily lives, so both teachers and students do not face difficulty in adjustment. This study aims to develop an innovative Android-based ethnomathematics learning media product for the topic of 3D shapes for elementary school students. This research is a research and development (R&D) study adopting the Alessi & Trollip model, which includes the stages of planning, design, and development. The subjects of this study include two media experts, two content experts, two fifth-grade teachers, and six sixth-grade students. Data were collected using non-test techniques with instruments in the form of validation questionnaires/feasibility questionnaires for media experts, content experts, teachers, and students. The data obtained from the questionnaires were analyzed descriptively to find the average score of each assessment. The results of the study show that the Android-based ethnomathematics learning media received an average total score of 4.65 from media experts, which falls into the